Etika Profesi Auditor dalam Nilai Budaya Tri Hita Karana - Rakhmawati, Aida (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p15, 2020)
Researcher tries to describe the ethical values ??of profession and accounting code of ethics of an auditor from the perspective of Tri Hita Karana. Tri Hita Karana used as the paradigm while literature and ethics of profession of auditors as author’s insight, Tri Hita Karana paired with prevailing code of ethics; AAOIFI, AICPA, and IAI. In conclusion, culture is important for character builder and human nature, it makes possibilities to open communication across religious and culture, creating cooperative communities, empowering people, eliminating gap between races and groups, and change the perception material things as the sole purpose of working. Keywords: Ethics; Auditor; Tri Hita Karana.